2017
DOI: 10.5812/jhealthscope.15125
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity and Its Association with Self-reported Infectious and Parasitic Diseases Among Household Mothers in Southeast of Iran

Abstract: Background: Nowadays, more than 1 billion people suffer from food insecurity worldwide. Food insecurity is recognized as an important determinant of health, and both food insecurity and diseases are public health concerns. This study aimed at determining the association between food insecurity and self-reported history of infectious and parasitic diseases among household mothers in Zahedan, southeast of Iran. Methods: This cross-sectional study was conducted on 2160 households in Zahedan. Food insecurity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…To our knowledge, few studies mainly emphasized the prevalence of HFI in patients with GI cancers, especially among Iranian patients. 2 , 5 , 20 Based on the results of this study, 35.2% of household participants were food-insecure with 19.9% of VLFS and 15.3% of LFS. In a study by Daneshi-Maskooni and colleagues which was performed on 120 patients with cancer with the aim of determining the prevalence of FI and its associated factors, the prevalence was 44%.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…To our knowledge, few studies mainly emphasized the prevalence of HFI in patients with GI cancers, especially among Iranian patients. 2 , 5 , 20 Based on the results of this study, 35.2% of household participants were food-insecure with 19.9% of VLFS and 15.3% of LFS. In a study by Daneshi-Maskooni and colleagues which was performed on 120 patients with cancer with the aim of determining the prevalence of FI and its associated factors, the prevalence was 44%.…”
Section: Discussionmentioning
confidence: 72%
“…were the other factors which their effects on FI in various studies were examined. 20,[53][54][55] Based on a study by Mohsena et al who evaluated the seasonality of FI levels in Bangladesh, environmental changes were among the other influential factors which also might affect adversely HFI. 56…”
Section: Discussionmentioning
confidence: 99%
“…The rate of food insecurity in the study area is analogues to the nding in the study carried in Kenya [19] Ethiopia [20] . However, the prevalence of food insecurity was 5.3% among all households studied in Republic of Korea [21] and 58.8% in Southeastern Iran [22] . One study conducted in Northeast of Iran reported the prevalence of food insecurity was 40.9% that related to income, infrastructure and rural distance [23] .Also in the Southeast Iran [22] who related the food insecurity to socioeconomic status of the households, ethnicity, education, age, and employment status of the head of the household and the mother of the household.…”
Section: Discussionmentioning
confidence: 85%
“…However, the prevalence of food insecurity was 5.3% among all households studied in Republic of Korea [21] and 58.8% in Southeastern Iran [22] . One study conducted in Northeast of Iran reported the prevalence of food insecurity was 40.9% that related to income, infrastructure and rural distance [23] .Also in the Southeast Iran [22] who related the food insecurity to socioeconomic status of the households, ethnicity, education, age, and employment status of the head of the household and the mother of the household. Same ndings was reported in Ethiopia [24] unemployment, no job, low household income and living in a leased or rented home was found associated with HH food insecurity [21] .…”
Section: Discussionmentioning
confidence: 85%
“…To determine the food security status of households based on their obtained score, the households were classified as food-secure, food-insecure without hunger, food-insecure with moderate hunger, and food-insecure with severe hunger ( 22 , 23 ).…”
Section: Methodsmentioning
confidence: 99%